URGENSI PEMBENTUKAN BADAN PERADILAN KHUSUS DALAM PENYELESAIAN SENGKETA HASIL PILKADA LANGSUNG - Yonata Harefa; Haposan Siallagan; Hisar Siregar (Magister Hukum Universitas HKBP Nommensen, 2020)
In accordance with the decision of the Constitutional Court Number 97 / PUU-XI / 2013, the Constitutional Court is no longer authorized to resolve disputes on direct election results, because the provisions of Article 236C of Law Number 12 Year 2008 NRI are against the Constitution of 1945. Article 157 paragraph (1) Law No. 8 Year 2015 determines that the dispute settlement on direct election results become the authority of specialized judiciary. But before a specialized judiciary is formed, then the Constitutional Court is authorized to resolve disputes on direct election results. The authority of the Constitutional Court is the constitutional authority to fulfill temporary legal vacuum (rechtvakum). Therefore legislators should immediately establish a specialized judiciary which has the authority to resolve the disputes on direct election results.